KETERLIBATAN STAKEHOLDER DALAM PENGEMBANGAN KUBU GADANG SEBAGAI DESA WISATA DI PADANG PANJANG - Surendra, Gilang; Jendrius, Jendrius; Indraddin, Indraddin (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2018)
Changes in the development paradigm in the era of democratization and regional autonomy, from centralistic to participatory, provide more opportunities for community involvement at the local level starting from planning, implementation and evaluation. One form of community involvement in tourism is through the development of tourist villages. One of these tourist villages is located in the city of Padang Panjang, West Sumatra, named Kubu Gadang. In the development of tourism, the role of stakeholders consisting of government, society and the private sector will not be separated from it. The key player in the development of Kubu Gadang as a tourist village is the Padang Panjang City Tourism Office, the subject is the Pokdarwis Kubu Gadang community and the Kubu Gadang community because they are actors and hosts in the Kubu Gadang tourist village. The context setter is the District Head of East Padang Panjang and, the Village Head of Kelurahan Ekor Lubuk, and the crowd is the Padang Panjang Archive and Library Office, the media and the Bank. Forms of involvement occur during planning and use of meetings as a medium for engagement.